Ejercicios de expansión pulmonar en pacientes con deformidades torácicas. - Antamba Varela, Emily Karolina (2024)
Introduction: Thoracic deformities are alterations that affect the lives of many patients, causing physiological, aesthetic, and psychological problems. Thus, respiratory physiotherapy is a treatment alternative that, in recent years, through scientific evidence, has sought to provide a second chance to improve the quality of life. Objective: Identify and recognize exercises applied to thoracic malformations such as pectus excavatum pectus carinatum and conditions related to their characteristics. Methodology: The present work is of documentary and bibliographic design based on databases such as Pudmed, Scopus, Virtual Health Library, NICE, Cochrane, and Science Direct for the quality of their information, in addition to descriptors through the use of Boolean operators (AND/OR/NOT), Inclusion criteria included articles less than 10 years of publication, with a score over seven on the Physiotherapy Evidence Database scale, over six on the Preferred Reporting Items for Systematic reviews and Meta-Analyses scale and over seven on the CASE REPORT assessment, and as exclusion criteria, information existing in systematic reviews was taken into account. Results: Through the search in the different databases, 88 articles were collected as a population, which were subjected to a selection process that depended on the year of publication, reading of the title, and the scores obtained in the evaluations according to each scale. This generated a sample of 26 articles, which included joint and separate information about the two variables proposed for the research work. Conclusions: Respiratory physiotherapy is vital and is presented as a therapeutic alternative to treat thoracic deformities derived from pectus. Studies demonstrate that thoracic expansion exercises decrease symptomatology, especially when combined with conventional physiotherapy, increasing the degree of success and adherence to treatments.